Tradisi Wiji Dadi sebagai Identitas Budaya Dalam Pernikahan Adat Jawa - Praharani, Nurfarida; Pradita, Silvy Mei; Sidik, Humar (Universitas Muhammadiyah Prof. Dr. Hamka, 2025)
This study aims to explore the existence of the Wiji Dadi tradition in Javanese traditional weddings in the Pesanggrahan area, as well as the efforts made by the local community to preserve it. A descriptive qualitative method with an ethnographic approach was employed to understand the meaning and role of this tradition in the social life of the community. The findings reveal that the Wiji Dadi tradition, particularly the egg-stepping ceremony, is still practiced today. This persistence is driven by the community’s deep affection for their ancestral heritage and the recognition of Wiji Dadi as a marker of Javanese ethnic identity. Beyond cultural preservation, the tradition also serves as a means of introducing Javanese wedding customs to broader society. Preservation efforts include educating the younger generation, organizing workshops and training sessions, promoting the tradition through social media, and integrating Wiji Dadi into modern wedding concepts without losing its essential meaning. These findings highlight the importance of innovative strategies to ensure the continuity of traditional practices amid the currents of globalization.